Pengeluaran Pemerintah Kabupaten/Kota di Provinsi Riau: Pendekatan Spasial - Tata Surya; Fery Andrianus; Neng Kamarni (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Traditional determinants of government spending include income, grants, demographic and political factors. But a government's spending policy can also be influenced by its neighboring governments' spending policies. This study uses Spatial Autoregressive (SAR) spatial econometrics to observe the existence of strategic interactions in District/City Government spending in the Riau Province for the 2011-2019 period. The research results show that there is a strategic interaction in government spending.